(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2017)
Background: Incisional Hernia (IH) is a preventable cause of morbidity and mortality, yet they are commonly encountered in our locale. Objective: This study was undertaken to determine the pattern of presentation of incisional hernia in our setting. Patients and methods: Consecutive patients aged 18 years and above, who presented with incisional hernia over a 5 year period (1st January 2010 to 31st December 2014) at the Surgical Out-Patient Clinics and Accident and Emergency Department of ABSUTH were studied. Results: Thirty five adult patients with IH were seen. Five (14.3%) patients were males and 30 (82.9%) were females. The age range was 24–79 years with a mean age of 50.1 years. Nineteen patients (54.3%) presented within 5 years of the pre-hernia surgery while 4 patients (11.4%) presented 15 or more years following the surgery. Thirty two (91.4%) patients presented with abdominal swelling, pain, unsightly abdominal wall singly or in combination, while 3(8.6%) patients presented with features of intestinal obstruction. All the patients had midline incisions. Obstetric and gynaecological operations in 29 patients (82.9%) were the leading pre-hernia operations. In 21 patients (60%), the pre- hernia surgeries were emergency surgeries. The pre-hernia operation wounds were infected in 25 patients (71.4%). Twelve (34.3%) patients had a single fascial defect, while 23 (65.7%) patients had multiple defects. The Body Mass Index (BMI) in 32 patients was more than 32Kg/m2. Fifteen (42.9%) patients have had multiple abdominal surgeries including previous unsuccessful repairs of the incisional hernia. The size of the defects on the fascia ranged between 6cm2 and 148cm2. Repair was by use of mesh in on lay technique in 33 cases ( Polypropylene mesh) and fascial closure in 2 cases. Conclusion: Obstetric and gynaecological operations using midline incisions were the commonest causes of incisional hernia in this study.